Exploring students’ experience on exchange programs. The case of Azerbaijani exchange students - Habibova, Gulzar (ADA University, 2024)
This qualitative exploratory research aimed to explore Azerbaijani students’ experiences in exchange programs and investigate perceived benefits and opportunities for them. Although it is proven that formal education is the cornerstone of the education system, exchange programs offer an opportunity for students to enhance their knowledge related to different specialized areas. Since non-formal education is an essential part of exchange programs, it is believed that they expand students’ worldviews and global perspectives. Convenient sampling was utilized to select participants who were accessible through personal contacts. Hence, the snowballing strategy assisted in finding more exchange students to participate in the study. A semi-structured interview analysis revealed that this study participants’ social life was affected significantly as their communication skills improved. The ability to work in a team was also positively affected. Moreover, improving language skills was discussed by the participants as significant progress that would contribute to both their social and professional lives in the future. The final aspect of social life that impacted positively was the cultural awareness of the participants who could familiarize themselves with different cultures in the programs. What is more, experiencing independent thinking and acquiring new research skills was shared as one of the perceived benefits of exchange programs. However, the participants also experienced some challenges such as grasping advanced economic concepts, picking up language skills, adaptation, and re-integration. Finally, the career development aspect of exchange programs was mentioned as the participants developed their self-confidence to work abroad after the exchange programs to some extent.
Keywords: Exchange of students -- Azerbaijan; Education, Nonformal -- Azerbaijan; Career development -- Azerbaijan; Education -- International aspects; Study and teaching (Higher); Student exchange programs -- Experiences; Education